Dysregulated dopamine storage increases the vulnerability to α-synuclein in nigral neurons - Ayse Ulusoy (Neurobiology of Disease, 2012)
Impairments in the capacity of dopaminergic neurons to handle cytoplasmic dopamine may be a critical factor underlying the selective vulnerability of midbrain dopamine neurons in Parkinson's disease. Furthermore, toxicity of α-synuclein in dopaminergic neurons has been suggested to be mediated by direct interaction between dopamine and α-synuclein through formation of abnormal α-synuclein species, although direct in vivo evidence to support this hypothesis is lacking. Here, we investigated the role of dopamine availability on α-synuclein mediated neurodegeneration in vivo. We found that overexpression of α-synuclein in nigral dopamine neurons in mice with deficient vesicular storage of dopamine led to a significant increase in dopaminergic neurodegeneration. Importantly, silencing the tyrosine hydroxylase enzyme – thereby reducing dopamine content in the nigral neurons – reversed the increased vulnerability back to the baseline level observed in wild-type littermates, but failed to eliminate it completely. Importantly, TH knockdown was not effective in altering the toxicity in the wild-type animals. Taken together, our data suggest that under normal circumstances, in healthy dopamine neurons, cytoplasmic dopamine is tightly controlled such that it does not contribute significantly to α-synuclein mediated toxicity. Dysregulation of the dopamine machinery in the substantia nigra, on the other hand, could act as a trigger for induction of increased toxicity in these neurons and could explain how these neurons become more vulnerable and die in the disease process.